Ruta de Aprendizaje: Transición hacia una Ganadería Silvopastoril Sostenible en Armonía con la Amazonía - Vanegas, Carlos José; Moreno, J. (International Livestock Research Institute, 2024)
This report documents the implementation of the "Pioneers of Adaptation" approach under the Program for Climate-Smart Livestock (PCSL) in Caquetá, Colombia, through a partnership between ILRI, Bioversity International-CIAT, and PROCASUR. The initiative supported small-scale cattle farmers in transitioning toward sustainable silvopastoral systems in a region where livestock is the main livelihood yet faces major environmental challenges. Following a survey of 300 households, 27 Adaptation Pioneers were identified for their innovative practices in sustainable cattle ranching, with notable participation of women. Using PROCASUR’s Learning Routes methodology, three routes were organized in November 2024, engaging 86 participants through field visits to exemplary farms. The routes enabled peer-to-peer learning, validation of good practices, and the co-design of innovation plans for improved livestock productivity, animal welfare, environmental management, and climate adaptation. The findings demonstrate how farmer-led innovation and experiential learning can strengthen local capacities, diversify production, and contribute to conservation and restoration of Amazonian landscapes.